EFFECT OF NITROGEN FERTILIZER SOURCES ON THE QUALITY AND MINERAL NUTRIENT COMPOSITION OF YAM - OKPON , S. N.; ADUAYI, E. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Field experiments were carried out to evaluate the effects of nitrogen fertilizer sources on quality and mineral nutrient composition of white yam (Dioscorea rotundata). Three rates of nitrogen; 0, 80 and 160 kg N/ha were applied in the forms of ammonium sulphate (AS) calcium ammonium nitrate (CAN) and urea for two yam growing seasons. Soil acidity was increased with increasing application of AS followed by urea, whereas CAN application resulted in higher pH. The application of urea and CAN at 160 kg N/ha increased -N whereas AS decreased N, P and K in the leaves. A highly positive significant correlation was established between leaf -N and starch and glucose content of the yam tuber. In general, AS fertilization produced the highest fresh tuber yield, percent starch and glucose while CAN produced the lowest yield, percent starch and glucose